COAL PACKING DENSITY ANALYSIS FOR TRANSPORT APPLICATION - (NIM 12104061), IRAMONA
Packing density is taking interest in many fields of engineering application, including coal transportation. The optimalization of packing density increases the efficiency and capacity of coal transport devices. Possibility of attaining a high packing density can be obtained by mixing graded particle sizes, arrange the particle proportion and size distribution. Arrangement the particle size distribution also can prevent the spontaneous combustion. This study have been carried out by coal packing experiment and simulation of optimation packing density models with existing experimental data singular packing density value for sphere found by experimental McGeary about 0,625 and from laboratory coal experiment about 0,586. The models assumpted with packing recursif, coarse particle poured particularly and followed by second particle population, etc. Shape particles model assumpt spherical particles because of its very well flowability. This model distinguish discrete distribution, two, three and four sizes. Binary packing can be generalized for mixtures with more than two components such as followed, with assumption that a second population of particles maybe packed with the same efficiency. Calculation assuming Qc= Qf = 0,625 and Qc=Qf =0,586 are compared with the experimental data of McGeary and with binary packing coal experimental. In general, the result of models both binary packing and more than two particles sizes, has given near value with the experimental McGeary, but reverse with coal experiment which have done in laboratory. Binary packing between large size of coal +3 mesh and small size of coal -3+12 mesh, -12+14mesh, -14+20 mesh, and -20+28 mesh which have been arranged by size ratio 4,786-5,678-7,882-11,167 the packing binary has given maximum packing density succesive about 59,9%-68,5%-70,4% dan 76,9%, respectively for mixtures consisisting 60% coarse fraction. Even if binary packing model with assuming Qc= Qf = 0,625 give maximum packing density surrounding 85,9% with 72,72% large particles, while binary packing model with assuming Qc= Qf = 0,586 give maximum packing density surrounding 82,9% with 70,7% large particles. The predicted relative proportions for quarternary mixtures of spheres, calculated assuming x = 0,625 respectively from the largest particles to the smallest, 63,8% - 23,9% - 9,0% - 3,4% and maximum packing density 98%. At the same time, quarternary packing have given maximum packing density 97,1% for assuming value x =0,586 with succesive proportion 60,4%- 25%-10,3%-4,3%. However, variation of coal size distibution and the used of predicted proportion as well as maximum packing density are utilized in coal transport optimalization, including coal transportation in barge or coal transshipment.